Barriers to accessing opioid substitution treatment for opioid use disorder: A systematic review from the client perspective. (1st April 2021) - Hall, Natasha Yvonne; Le, Long; Majmudar, Ishani; Mihalopoulos, Cathrine
Highlights: 19 barrier subthemes to OST initiation emerged, the most reported barrier subtheme was negative perception of treatment (59 %). Overarching barrier themes were related to stigma and fear, regulatory, logistical, attitudinal and social factors. 37 studies, 18 qualitative, 15 quantitative and four mixed methods were included in the review. The most common reported barrier subtheme in quantitative studies was cost (67 %). Abstract: Objectives: To update the existing evidence to identify specific barriers to initiation of opioid substitution therapy (OST) for those with opioid use disorder (OUD). Methods: The review follows Preferred Reporting Items for Systematic Reviews andMeta-Analyses (PRISMA) guidelines. Six databases were initially searched in November 2019, with the search updated on 11 November 2020, for qualitative or quantitative studies reporting the barriers to initiating OST from the client with OUD perspective. Thematic analysis of the barriers to OST was undertaken to determine barrier themes and subthemes. Results: There were 37 studies included in the review; 18 were qualitative, 15 were quantitative and four were mixed methods. The barrier themes identified were stigma and fear, regulatory, logistical, attitudinal and social factors. Within these barrier themes 19 barrier subthemes were identified. The most reported OST barrier subthemes were negative treatment perceptions, cost, stigma and lack of flexibility. Conclusion: This review discusses important barriers to OST and examines reported barriers from the client perspective. OST guidelines and programs would benefit by introducing programs that reduce stigma, increase treatment knowledge and health literacy, reduce treatment costs, increase treatment flexibility and allow for easier treatment access.